Geography of Cika cattle breed - Žan Lotrič, Metka (Acta agriculturae Slovenica, 2012)
The geography of Slovenian autochthonous Cika cattle breed was studied over a 140-year period of its development. The first literature reference regarding the dissemination range of original Cika cattle was found in the year 1872, when Schollmayr (1873) studied cattle breeds in Carniola. In the second half of the 19 century, cattle in Carniola were without their own names of breeds and were characterized by a large phenotypic diversity. A generic term "Carniolan cattle" was the most commonly used name and animals were grouped according to their colour. Povše (1893) reported that the red coloured Gorenjska cattle were to the fullest extent spread in the area which today belongs to Gorenjska statistical region. Under the influence of specific climate and breeding conditions in Bohinj area, the smallest in size and the most dairy type of Cika cattle was developed here. They named it as "Bohinj cattle" and this was the original form of Cika cattle. Breeding of Cika cattle maintained in the same area until the sixties of the past century. In the year 1964 a symposium took place in Kranj, where it was decided that Cika cattle was going to get upgraded bz Simmental breed. Today, the breeding of Cika cattle is dispersed across a larger area of the Republic of Slovenia, however, it is the most widespread in the north part of Central Slovenian statistical region (Kamnik area) and Gorenjska, especially in the south-eastern part of Julian Alps (Bohinj area). In these two areas, Cika cattle breeding is still most concentrated.
Keywords: cattle; govedo; autochthonous breed; avtohtone pasme; Cika cattle; cikasto govedo; geography; izvorno območje; origin area; Slovenija; Slovenia